2018
DOI: 10.1155/2018/3830104
|View full text |Cite
|
Sign up to set email alerts
|

HLA-C Alleles and Cytomegalovirus Retinitis in Brazilian Patients with AIDS

Abstract: Purpose Since cytomegalovirus retinitis (CR) is an important cause of visual impairment among AIDS patients and HLA-C alleles have been associated with AIDS disease outcome, we typed HLA-C locus in patients with AIDS exhibiting or not CR. Methods Three groups of individuals were studied: (i) 49 patients with AIDS and CR (Group I), (ii) 161 patients with AIDS without CR (Group II), and (iii) 202 healthy HIV-negative individuals (Group III). HLA-C typing was performed using commercial kits. Results The HLA-C∗07 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…In the context of TB, a higher prevalence of KIR2DL3 among TB patients has been observed in several studies [15,18,90,91]. Biberg-Salum et al [92] showed that HLA-C * 07 allele conferred protection against the development of cytomegalovirus retinitis in Brazilian AIDS patients.…”
Section: Discussionmentioning
confidence: 95%
“…In the context of TB, a higher prevalence of KIR2DL3 among TB patients has been observed in several studies [15,18,90,91]. Biberg-Salum et al [92] showed that HLA-C * 07 allele conferred protection against the development of cytomegalovirus retinitis in Brazilian AIDS patients.…”
Section: Discussionmentioning
confidence: 95%
“…Besides HLA-G , other genes of the Major Histocompatibility Complex have been previously associated with CMV-R, including: (1) the overrepresentation of TNF microsatellites ( TNFc2 alleles, as well as the 4-1-G-2-2-1 haplotype, which contains the TNFc2 allele) in patients with AIDS, inducing a rapid progression of the disease as well as the development of accelerated CMV-R 27 , (2) the HLA-A31 antigen was associated with the development of AIDS, irrespective of the presence or not of CMV-R 17 , (3) the HLA-C*07 allele group was assoaciated with protection against the development of CMV-R when compared to patients with AIDS without CMV-R. In addition, the HLA-C *05 allele group was associated with susceptibility to and the HLA-C*16 allele group with protection against AIDS development, irrespective of the presence or not of CMV-R 19 , and (4) the HLA-B35 antigen was associated with the rapid progression of AIDS and development of retinochoroidites induced by Toxoplasma gondii 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Although studies regarding the classical HLA class I and class II profiles of patients with AIDS exhibiting ocular manifestations have been reported so far 17 19 , there is no information regarding the study of the non-classical HLA-G gene in patients exhibiting both AIDS and CMV-R. The present study was undertaken based on the hypothesis that variation sites at the HLA-G 3′UTR in patients with AIDS exhibiting or not CMV-R may discriminate variation sites associated with the regulation of the immune checkpoint gene.…”
Section: Introductionmentioning
confidence: 99%
“…Возможно, широкое применение высокоактивной антиретровирусной терапии (ВААРТ), которая существенно улучшает прогноз пациентов с ВИЧ, оказало влияние на частоту глазных проявлений инфекции. Кроме того, скорость прогрессирования основного заболевания связана с некоторыми аллелями комплекса гистосовместимости (в частности, аллель HLA-C*07 защищает от развития цитомегаловирусного ретинита (ЦМВ-ретинита) при ВИЧ-инфекции) [8].…”
Section: эпидемиология цитомегаловирусного ретинита при вич-инфекцииunclassified
“…Ретинит, вызванный вирусом цитомегалии, является наиболее частой причиной снижения зрения при ВИЧ и при отсутствии лечения может приводить к слепоте [1-3, 8, 10-12]. Внедрение ВААРТ в клиническую практику привело к значительно-му снижению частоты выявления этой патологии и уменьшению числа тяжёлых и запущенных случаев [1,8,10]. Согласно некоторым данным частота ретинитов снизилась на 75 % [1,10].…”
Section: эпидемиология цитомегаловирусного ретинита при вич-инфекцииunclassified